Soft Skills and European Labour Market: Interviews with Finnish and Italian Managers - Kai Johannes Schleutker; Valeria Caggiano; Fabiana Coluzzi; Jose Luis Poza Luján (LED Edizioni Universitarie, 2019)
Recent reports have suggested that many employees in the labour market today lack essential soft skills. Yet, the specific relevance of these skills for particular job occupations is still to explore. We investigated perceptions of skill requirements and their development potential reflected against cultural impacts, using close interviews of 64 managers at firms in different fields of industries in Italy and Finland. Managers reported that, due to heightened competitive pressure, specific soft skills, particularly Work in team and flexibility to develop, are becoming increasingly important. The study indicates that the perceived significance of soft skills seems to vary according to the working environment and occupation. Furthermore, some soft skills seem to have a higher potential for development and thus suggested to be implemented in the university curricula. The paper concludes that a country characterized by working  environments conducive to the development of soft skills, must however promote research for the identification and relevance of the skills themselves.